2010
DOI: 10.2353/ajpath.2010.090442
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Gremlin1 (GREM1) Promoter CpG Island Hypermethylation in Clear Cell Renal Cell Carcinoma

Abstract: Gremlin1 (GREM1), a bone morphogenetic protein antagonist and putative angiogenesis-modulating gene, is silenced by promoter hypermethylation in human malignancies. Here we study GREM1 methylation in clear cell renal cell carcinoma (ccRCC) and its impact on tumor characteristics and clinical outcome. Three GREM1 promoter CpG island regions (i, ii, iii) were analyzed by methylation-specific PCR and/or bisulfite sequencing in ccRCC cell lines and ccRCCs from two independent patient series. Results were correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 61 publications
1
62
1
Order By: Relevance
“…These hypermethylation markers are promising tools to detect cancer cells in tissue and body fluids (6,7) with the use of simple PCR technology (8)(9)(10). Proof of principle for the clinical value of methylation markers has been reported for early detection and classification of cancer (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), risk assessment and prognosis (19,(22)(23)(24), and prediction of therapy response (25)(26)(27), with some already having shown their importance in (pre)clinical practice. Thus, the promise of methylation changes to become a powerful diagnostic and predictive tool (6) is becoming a reality.…”
Section: Introductionmentioning
confidence: 99%
“…These hypermethylation markers are promising tools to detect cancer cells in tissue and body fluids (6,7) with the use of simple PCR technology (8)(9)(10). Proof of principle for the clinical value of methylation markers has been reported for early detection and classification of cancer (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), risk assessment and prognosis (19,(22)(23)(24), and prediction of therapy response (25)(26)(27), with some already having shown their importance in (pre)clinical practice. Thus, the promise of methylation changes to become a powerful diagnostic and predictive tool (6) is becoming a reality.…”
Section: Introductionmentioning
confidence: 99%
“…Although GREM1 was frequently methylated in RCC, Morris and colleagues [27] could not find an association with patient survival. In contrast, our group and Ricketts' group [29][30][31] Figure 4C). In a subsequent study of Morris' group [32], nine genes were identified to be frequently methylated in primary RCC tumor samples.…”
Section: Assay Methodsmentioning
confidence: 54%
“…Besides choice of method and cut-off value, also the exact genomic location of the analyzed CpG dinucleotides is important [74]. This was illustrated by van Vlodrop and colleagues [30], who showed that GREM1 methylation varies within the promoter CpG island, with also methylation-region-specific effects on patient outcome.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For DAPK-1 as well as for SCUBE3 an association with an increased risk of recurrence has been shown (10,33). Van Vlodrop et al were also able to show significantly worse survival to be associated with methylation of one region within the GREM-1 CGI in univariate analysis and decreased overall survival in correlation with hypermethylation of another GREM-1 CGI subregion in multi-and univariate analysis (34). By creating a combined methylation score for the Wnt-Antagonists sFRP-1, sFRP-2, sFRP-4, sFRP-5, Wif-1 and Dkk-3 Urakami et al instead of were able to show statistical association with a shortened overall survival found SFRP1, BNC1 and COL14A1 to be related with poor prognosis (9,35).…”
Section: Discussionmentioning
confidence: 69%